A biomechanical paradox in fish: swimming and suction feeding produce orthogonal strain gradients in the axial musculature - Yordano E. Jimenez (Nature Portfolio, 2021)
Abstract The axial musculature of fishes has historically been characterized as the powerhouse for explosive swimming behaviors. However, recent studies show that some fish also use their ‘swimming’ muscles to generate over 90% of the power for suction feeding. Can the axial musculature achieve high power output for these two mechanically distinct behaviors? Muscle power output is enhanced when all of the fibers within a muscle shorten at optimal velocity. Yet, axial locomotion produces a mediolateral gradient of muscle strain that should force some fibers to shorten too slowly and others too fast. This mechanical problem prompted research into the gearing of fish axial muscle and led to the discovery of helical fiber orientations that homogenize fiber velocities during swimming, but does such a strain gradient also exist and pose a problem for suction feeding? We measured muscle strain in bluegill sunfish, Lepomis macrochirus, and found that suction feeding produces a gradient of longitudinal strain that, unlike the mediolateral gradient for locomotion, occurs along the dorsoventral axis. A dorsoventral strain gradient within a muscle with fiber architecture shown to counteract a mediolateral gradient suggests that bluegill sunfish should not be able to generate high power outputs from the axial muscle during suction feeding—yet prior work shows that they do, up to 438 W kg−1. Solving this biomechanical paradox may be critical to understanding how many fishes have co-opted ‘swimming’ muscles into a suction feeding powerhouse.